Development of synchronous Reluctance motor associated to pumping water well related to PV panels - CHAIB Zoubir; DOUIB Ali; NESRAT Oualid; RAMDANI Hacen (University of Shahid Hama Lakhdar - El Oued, 2024)
The most common problem in remote places and the most isolated communities that are far from waterways and electricity grid. To ensure the water supply anywhere, we have to use a standalone power supply, and photovoltaic solar energy is one of the most common of these energies. This combination is called "Photovoltaic Water Pumping System" . This system is the perfect way to fix the water supply's problems, by extracting and pumping the water from a well even in rural areas and places, and that is the system’s goal. The photovoltaic water pumping system can be used in many domains, including residential, farming (irrigation, breeding, and agriculture), water purification, or firefighting. It combines two principle parts that are the photovoltaic system and the pumping system. Accordingly, in this research we studied and modeled a pumping system connected to a synchronous reluctance motor. المشكلة الأكثر شيوعا في الأماكن النائية والمجتمعات الأكثر عزلة البعيدة عن الممرات المائية وشبكة الكهرباء. لضمان إمدادات المياه في أي مكان، يتعين علينا استخدام مصدر طاقة مستقل، والطاقة الشمسية الكهروضوئية هي واحدة من أكثر هذه الطاقات شيوعا. يسمى هذا المزيج "نظام ضخ المياه الكهروضوئية". هذا النظام هو الطريقة المثلى لإصلاح مشاكل إمدادات المياه، من خلال استخراج وضخ المياه من بئر حتى في المناطق والأماكن الريفية، وهذا هو هدف النظام. يمكن استخدام نظام ضخ المياه الكهروضوئية في العديد من المجالات، بما في ذلك السكنية أو الزراعية )الري والتربية والزراعة( أو تنقية المياه أو مكافحة الحرائق. فهو يجمع بين جزأين رئيسيين هما النظام الكهروضوئي ونظام الضخ.. وعليه قمنا في هذا البحث بدراسة ونمذجة نظام الضخ متصل بمحرك ممانعة متزامن.
Mémoire de master en électromécanique
Keywords: Photovoltaic energy; Centrifugal Pumps; SynRM; الطاقة الكهروضوئية، مضخات الطرد المركزي، محركات الممانعة المتزامنة SynRM .